Exploring the use of authentic learning strategies in designing blended learning environments. Issue 2 (6th July 2015) - Tan, Heidi, Yeen-Ju; Neo, Mai
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The aims of this study is to use authentic learning principles outlined by Herrington and Kervin (2007) as an innovative approach towards the development of a blended learning environment in a Malaysian classroom at the tertiary level and students' perception towards this learning environment was studied. Design/methodology/approach – This study was conducted using a mixed-method approach and consisted of two parts. Part A: the learning environment was designed to be student-centred, supported by multimedia and web technologies, consisting of online learning modules, blogs and social media, as well as being driven by a class project. Part B: qualitative and quantitative data were collected to solicit student feedback on the learning environment. Findings – Results of the study indicated that students responded positively towards the authentic blended learning environment, as it was found to be relevant to their learning. In an authentic blended learning environment, students became more engaged with the content and actively involved in their learning process. These results show strong and encouraging support for the use of authentic learning principles in the development of blended learning environments. Originality/value – Universities in Malaysia are only beginning to move towards a more blended approach in designing learning environments. This paper provides some insights to one possible way of designing a blended learning environment in a Malaysian tertiary setting.